2018
DOI: 10.1101/308304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strength in numbers: collaborative science for new experimental model systems

Abstract: 25Our current understanding of biology is heavily based on the contributions from a 26 small number of genetically tractable model organisms. Most eukaryotic phyla lack such 27 experimental models, and this limits our ability to explore the molecular mechanisms that 28 ultimately define their biology, ecology, and diversity. In particular, marine protists suffer 29 from a paucity of model organisms despite playing critical roles in global nutrient cycles, food 30 webs, and climate. To address this deficit, an … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…In all these organisms, multispectral fluorescence imaging showed that multiple TUs are successfully expressed from uLoop plasmids. Special attention was devoted to testing uLoop in P. tricornutum, recognising the special needs for genetic tools in such emerging model organisms and the need for new marine microbial model systems (39). The uLoop plasmids were efficiently introduced in P. tricornutum, in which exconjugants exhibited variable levels of fluorescent protein expression.…”
Section: Use Of Uloop Vectors Across Biological Kingdomsmentioning
confidence: 99%
“…In all these organisms, multispectral fluorescence imaging showed that multiple TUs are successfully expressed from uLoop plasmids. Special attention was devoted to testing uLoop in P. tricornutum, recognising the special needs for genetic tools in such emerging model organisms and the need for new marine microbial model systems (39). The uLoop plasmids were efficiently introduced in P. tricornutum, in which exconjugants exhibited variable levels of fluorescent protein expression.…”
Section: Use Of Uloop Vectors Across Biological Kingdomsmentioning
confidence: 99%
“…The phosphorylation dataset spans the Tree of Life but is unsurprisingly biased towards animal, fungal, and plant species. Ongoing projects for increased representation of the protist superkingdoms could help to address this problem in the future (Waller et al 2018). From this analysis also we conclude that most eukaryotic phosphomotifs post-date the divergence of eukaryotes and prokaryotes.…”
Section: Discussionmentioning
confidence: 66%
“…This transformation will be unlocked by coupling genomic data with current high-throughput approaches such as in vitro TF sequence binding affinity assays, genome-wide profiling of TF binding, and proteomics studies of chromatin beyond model species [50]. Additionally, the establishment of genetic manipulation tools in species representing unsampled eukaryotic lineages will crucially open the window to both targeted studies and genetic screens [51,52]. The comparative analysis and interpretation of these data will ultimately allow us to uncover general principles of TF regulation across eukaryotes and it will contribute to reconstruct the cellular and regulatory biology of the LECA.…”
Section: Discussionmentioning
confidence: 99%